ACOUSTIC EFFECTS OF DURATIONAL CUES IN THE PERCEPTION OF NAJDI ARABIC VOWEL CONTINUA - Mahmoud Al Mahmoud (Language Literacy: Journal of Linguistics, Literature, and Language Teaching, 2021)
This paper explores how the manipulation of vowel duration as a perceptual cue influences listeners’ perceptual ability. Four native speakers of Najdi Arabic, a well-known variety of Arabic in the Arabian Peninsula, were tested on the perception of /a/ vs. /ɛ/ vowels. Listeners’ identification and discrimination rates along each vowel continuum showed a clear effect of duration on the perception of /a/-/ɛ/ contrast. In each vowel continuum, listeners were more inclined to classify stimuli as belonging to one vowel or the other based on relative proximity to the steady-state vowel duration. Perceptibility naturally improved as duration approximated the normal duration of either vowel. Listeners’ perceptual judgments in the identification and discrimination of the vowels were swayed by their aural sensitivity to perceptual shifts (/a/-/ɛ/ at 185-195ms; /ɛ/-/a/ at 195-205ms). Moreover, findings of the identification task followed predictably from the discrimination task; this could be taken as evidence for the existence of categorical perception. Results aggregately indicate that perception of the two Najdi Arabic vowels proceeded as a function of duration.